2004
DOI: 10.1161/01.hyp.0000123572.45556.a5
|View full text |Cite
|
Sign up to set email alerts
|

Human Endothelium: Target for Aldosterone

Abstract: Abstract-Aldosterone has long been known to control water and electrolyte balance by acting on mineralocorticoid receptors in kidney. However, recent studies demonstrated the presence of these receptors in nonclassical locations, including the cardiovascular system. We tested the hypothesis whether endothelial cells respond to aldosterone with changes in cell volume, a measure for ion-mediated water movement across the cell membrane. By means of atomic force microscopy in fluid, we measured volume of adherent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
103
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 125 publications
(109 citation statements)
references
References 33 publications
4
103
0
1
Order By: Relevance
“…Similar to kidney tubules, endothelia also express ENaC (8,11), and aldosterone that modulates the insertion of channels into the apical membrane of distal tubule cells is its major regulator (9). Results obtained in long-term experiments indicate that, after the exposure to aldosterone, endothelial cells swell (9), stiffen, and simulta- Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar to kidney tubules, endothelia also express ENaC (8,11), and aldosterone that modulates the insertion of channels into the apical membrane of distal tubule cells is its major regulator (9). Results obtained in long-term experiments indicate that, after the exposure to aldosterone, endothelial cells swell (9), stiffen, and simulta- Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The aldosterone concentration used in our culture media is in the high normal range in the normal population (26). The sodium-induced increase in cell stiffness is most likely linked to cell swelling because in aldosterone-treated endothelium amiloride reverses the increase in cell volume (9) and cell pressure (20). However, these data should be interpreted with particular care.…”
Section: Role Of Epithelial Sodium Channels In Modulating Endothelialmentioning
confidence: 99%
See 2 more Smart Citations
“…They also demonstrated that cultured human umbilical vein endothelial cells responded to aldosterone with sodium and water entry and swelling that was blocked by spironolactone. 21 Swollen aldosterone-treated endothelial cells shrunk when amiloride was applied at concentrations that do not inhibit the sodium-proton exchanger (NHE) or with cariporide, a selective inhibitor of NHE, indicating that a sodium channel similar to the epithelial sodium channel of the distal nephron was involved in this aldosterone effect. Amiloride hyperpolarizes the cell as a result of the blockade of sodium channels, inducing chloride and water efflux, and cell shrinking.…”
Section: Endotheliummentioning
confidence: 99%